PERAN GURU DALAM INOVASI PEMBELAJARAN - Zunidar Zunidar (Universitas Islam Negeri Sumatera Utara, 2019)
The role of teachers is very strategic in determining the direction and model of learning in the classroom and outside the classroom. For that teacher serves as a manager and leader who designed various renewal program and practice pembeajaran. Managerial and leadership capabilities are expected to generate new innovations in membelajarkan protege. In this case it could be a learning innovation development of learning models, strategies, and the use of various media studied which allows students the best learning results.